Oral Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.8676
|View full text |Cite
|
Sign up to set email alerts
|

Lb0001 efficacy and Safety of Filgotinib for Patients With Rheumatoid Arthritis With Inadequate Response to Methotrexate: Finch1 Primary Outcome Results

Abstract: BackgroundFilgotinib (FIL) is an orally administered, potent and selective inhibitor of Janus kinase 1 (JAK1) that has shown good efficacy and was well tolerated for treatment of rheumatoid arthritis (RA).ObjectivesTo evaluate efficacy and safety of FIL treatment in patients with RA who have had an inadequate response to methotrexate (MTX).MethodsThis phase 3, double-blind, active- and placebo (PBO)-controlled study randomized patients with active RA (3:3:2:3) to FIL 200 mg, FIL 100 mg, active comparator (adal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 0 publications
1
38
0
1
Order By: Relevance
“…While two studies designed as non-inferiority trials have shown statistical superiority of baricitinib or upadacitinib compared with adalimumab (all in combination with MTX),80 81 a third study using tofacitinib+MTX did not show such superiority82; thus, the overall clinical relevance of small differences in clinical trials was not considered convincing enough for the task force to prefer tsDMARDs over bDMARDs. This conclusion is further supported by recently presented data revealing that filgotinib+MTX met non-inferiority for Disease Activity Score 28 <3.2, but not superiority criteria, when compared with adalimumab, a prespecified endpoint, although superiority was observed for some of the secondary endpoints 83. Importantly, in these studies various inflammatory markers, such as swollen joint counts, did not differ among the groups, in line with the hitherto unknown clinical relevance mentioned above.…”
Section: Resultssupporting
confidence: 82%
“…While two studies designed as non-inferiority trials have shown statistical superiority of baricitinib or upadacitinib compared with adalimumab (all in combination with MTX),80 81 a third study using tofacitinib+MTX did not show such superiority82; thus, the overall clinical relevance of small differences in clinical trials was not considered convincing enough for the task force to prefer tsDMARDs over bDMARDs. This conclusion is further supported by recently presented data revealing that filgotinib+MTX met non-inferiority for Disease Activity Score 28 <3.2, but not superiority criteria, when compared with adalimumab, a prespecified endpoint, although superiority was observed for some of the secondary endpoints 83. Importantly, in these studies various inflammatory markers, such as swollen joint counts, did not differ among the groups, in line with the hitherto unknown clinical relevance mentioned above.…”
Section: Resultssupporting
confidence: 82%
“…The efficacy and safety of filgotinib as both an add-on to methotrexate (MTX) and a monotherapy have been demonstrated in two 24-week phase 2b studies in adult patients with moderately-toseverely active RA and an inadequate response to MTX (MTX-IR) [5,6]. These results were confirmed and extended in three phase 3 randomized clinical trials in MTX-IR, MTX-naïve, and biologic disease-modifying anti-rheumatic drug-IR moderately-to-severely active RA, which met 12-or 24-week primary endpoints for efficacy [8][9][10].…”
Section: Introductionmentioning
confidence: 82%
“…27 This meta-analysis included 4 RCTs; namely ORAL Strategy, RA-BEAM, FINCH1 & Fleischman 2019. 22,26,28,29 This meta-analysis showed that in RA patients with an inadequate response to MTX, baricitinib 4mg + MTX and upadacitinib 15mg + MTX showed the highest ACR response rates. Additionally, it demonstrated a significantly higher ACR20 response rate with both baricitinib 4mg + MTX and upadacitinib 15mg + MTX when compared to adalimumab 40mg + MTX.…”
Section: Comparative Efficacy Of the Approved Jak Inhibitors For Ramentioning
confidence: 96%